The Efficacy of Chemo-Cooling Gloves in Preventing Nail Toxicity among Thai Women Undergoing Chemotherapy: A Quasi-experimental Study - Yodchai, Kantaporn; Hubjaroen, Sakorn; Maneekrong, Ketsaree; Uthaipan , Nattapon (Pacific Rim International Journal of Nursing Research, 2024)
Cryotherapy is widely used in health contexts, including first aid, treating acute musculoskeletal injuries and women undergoing chemotherapy. Studies have shown that frozen gloves can help reduce nail toxicity for women undergoing chemotherapy. Nail toxicity is a common issue among people undergoing chemotherapy, causing disfigurement and pain. Although cooling gloves have been shown to reduce nail toxicity, the range of temperatures used remains unclear, often resulting in discomfort. In this innovative study, we used a quasi-experimental, two group pretest-posttest design to evaluate the effectiveness of Chemo-Cooling Gloves developed by the researchers to help prevent nail toxicity. We assessed satisfaction with the gloves among 27 Thai women undergoing chemotherapy who were purposively recruited according to the inclusion criteria from a chemotherapy center of a university-affiliated hospital in a southern region of Thailand. Participants underwent a regimen of cyclophosphamide in combination with doxorubicin and 5-fluorouracil every 21 days for six cycles. Each participant served as their own control, wearing the cooling glove on the one hand randomly selected, while the other hand remained unprotected and acted as the control. Data were collected using a demographic questionnaire, the Common Terminology Criteria for Adverse Events version 3.0, and the Chemo-Cooling Gloves Satisfaction Questionnaire. Data analysis utilized descriptive statistics and Cochran’s Q test. The results revealed that nail toxicity was significantly lower in the protected hand than in the control hand during cycles 2 to 3 and 2 to 4, but no significant difference between the two hands during cycles 2 to 5 and 2 to 6. Overall satisfaction with the Chemo-Cooling Gloves was at the highest level. The use of frozen gloves aligns with evidence-based practice, as supported by our study. Nurses need to be trained in the proper use and application of the gloves and educate patients on the benefits and correct usage to maximize comfort and efficacy. By incorporating the Chemo-Cooling Gloves into routine practice, nurses can help improve patient adherence to chemotherapy regimens and potentially enhance treatment outcomes.